IDENTIFIKASI SANITASI LINGKUNGAN DASAR RUMAH TANGGA MELALUI SURVEY DI DESA WAETAWA DAN WAELIKUT KABUPATEN BURU SELATAN PROVINSI MALUKU - Tulalessy, Abraham Hendry; Sarfan, Riri; Wattimena, Marlin Chrisye; Rifyan Ruman (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Household sanitation plays a critical role in preventing diseases and health issues arising from environmental risk factors, contributing to the creation of a healthy environment across physical, chemical, biological, and social dimensions. Efforts to improve this include increasing access to clean water, adequate sanitation facilities, and the promotion of hygienic behavior. This community service program aimed to assess environmental sanitation conditions and identify strategies to improve health status. The method used involved surveys and direct observation of 20 respondents. The results showed that the majority of respondents were male (60%), aged between 30–39 years (40%), and worked as farmers or livestock breeders (55%). Most had an income of less than IDR 500,000 (35%). In terms of housing, 60% lived in privately owned homes, 40% had pesimas (bathing and washing facilities), 40% used dug wells, 65% had tiled floors, and 100% had brick walls. Regarding sanitation practices, 75% disposed of household waste daily by collecting and burning it, 90% used household toilets, and 85% had seepage-type latrines. Additionally, 75% of toilets were located more than 10 meters from clean water sources. In the past month, 50% of families reported members experiencing coughs and colds, 35% reported fever and headaches, and 75% indicated recent illness. When sick, 85% sought treatment at health centers, while 15% visited community clinics. Most respondents practiced daily routines that included religious study, family recreation, saving money, reading the news, and participating in local organizations. Cultural values were also reflected in community life, such as openness to newcomers, respect for elders (e.g., the mosque imam), occasional conflict, active participation in mutual cooperation, and strong social cohesion. In general, respondents demonstrated clean and healthy living habits; however, there are still areas that need improvement, particularly regarding the adoption of a nutritious and balanced diet. --- Sanitasi rumah tangga adalah hal penting dalam pencegahan penyakit dan masalah kesehatan akibat risiko lingkungan bertujuan untuk menciptakan lingkungan yang sehat secara fisik, kimiawi, biologis, dan sosial. Upaya yang dilakukan meliputi peningkatan akses terhadap air bersih, fasilitas sanitasi, serta penerapan perilaku hidup bersih dan higienis (WASH). Maksud dari kegiatan pengabdian guna mengetahui kondisi sanitasi lingkungan serta langkah-langkah perbaikan kondisi kesehatan masyarakat. Pendekatan yang diterapkan yaitu metode survey dan observasi langsung pada 20 responden. Hasil pengabdian menunjukkan mayoritas karakteristik responden adalah laki-laki (60%) usia 30-39 tahun (40%) memiliki pekerjaan sebagai petani/peternak (55%); penghasilan per bulan <Rp500.000 (35%). Karakteristik rumah responden hak milik (60%); dilengkapi pesimas (40%); sumur galian (40%); lantai rumah ubin (65%); dinding rumah batako (100%). Responden melakukan pembuangan sampah harian dengan mengumpulkannya terlebih dahulu, lalu membakarnya (75%); responden mempunyai jamban (90%); jenis jamban rembesan (85%); kedekatan lokasi jamban terhadap air bersih >10 meter (75%). Responden menyatakan dalam satu bulan terakhir terdapat pihak keluarga yang sakit batuk dan pilek (50%); demam dan sakit kepala (35%), responden mengetahui penyebab sakitnya (75%), jika sakit responden berobat ke puskesmas (85%) dan Pustu (15%). Mayoritas responden menerapkan kebiasaan sehari-hari seperti: belajar agama, rekreasi keluarga, mempunyai tabungan, membaca berita dan berorganisasi. Responden menerapkan nilai-nilai budaya dalam hidup berdampingan warga seperti: mudah menerima orang baru, orang yang ditetuakan adalah Imam Mesjid, intensitas konflik kadang-kadang terjadi, masyarakat aktif melakukan gotong royong, dan kondisi kebersamaan masyarakat sangat baik. Umumnya para responden sudah menjalani gaya hidup bersih dan sehat, meskipun masih terdapat aspek dimana perlu dioptimalkan, seperti penerapan pola makan yang bergizi dan seimbang.